Hypergolic Triggers as Co‐crystal Formers: Co‐crystallization for Creating New Hypergolic Materials with Tunable Energy Content. (6th November 2019) - Titi, Hatem M.; Arhangelskis, Mihails; Rachiero, Giovanni P.; Friščić, Tomislav; Rogers, Robin D.
Abstract: We demonstrate a co‐crystal‐based strategy to create new solid hypergols, that is, materials exhibiting spontaneous ignition when in contact with an oxidant, from typically non‐hypergolic fuel molecules. In these materials, the energy content and density can be changed without affecting the ignition delay. The use of an imidazole‐substituted decaborane as a hypergolic "trigger" component in combination with energy‐rich but non‐hypergolic nitrobenzene or pyrazine yielded hypergolic co‐crystals that combine improved combustion properties with ultrashort ignition delays as low as 1 ms. Abstract : … und es hat Boom gemacht : Cokristallisation eines hypergolischen Decaboran‐Bausteins, der entwickelt wurde, um Wasserstoffbrücken mit energetischen, aber nicht hypergolischen oder explosiven Brennstoffmolekülen einzugehen, ermöglicht die einfache und schnelle Synthese neuartiger hypergolischer Materialien mit abstimmbaren energetischen Eigenschaften und ultrakurzen Zündungsverzögerungen von bis zu 1 ms.